Low temperature co-fired ceramics technology for active eddy current turbocharger speed sensors. Issue 3 (2nd July 2018) - Ihle, Martin; Ziesche, Steffen; Gierth, Paul; Tuor, Andreas; Tigelaar, Jonathan; Hirsch, Oliver
Abstract : Purpose: The purpose of this paper is to analyze a presentation of eddy current sensing coils for the turbo charger speed measurement, which were manufactured with the low temperature co-fired ceramic (LTCC) technology. The goal is to be able to manufacture small robust coils with complex geometries and improved signal output. Design/methodology/approach: A crucial element for its performance is the quality factor of the embedded coil. Thanks to the use of the developed LTCC manufacturing processes, the lateral wounding distance of the printed coils can be reduced to 30 µm, and simultaneously, the aspect ratio should be enlarged compared to standard LTCC technologies. By the use of a novel printed double-D coil design, the overall sensor characteristics will be improved. Findings: The metallization thickness can be simultaneously enhanced that results in the internal resistance being reduced. Thus, the inductivity and the ohmic resistance achieve an obvious optimization that results in significant improvement of the quality factor of the novel coils when compared to standard technologies. Embedded micro coils have a sintered metallization aspect ratio of more than one and thus an optimal performance differing clearly from prior art. Their reliability was proven through temperature cycle tests of over more than 1, 300 h. Research limitations/implications: The developed LTCC coil technology will be introduced in the JAQUET sensor portfolio of TE Connectivity for the measurement of turbocharger speed on both passenger cars and trucks. The measurement and control of turbochargers speed enables the optimal regulation of airflow into the engine thereby improving the fuel economy and leading to a reduction of engine emissions. Originality/value: This paper shows fabrication and performance of the original manufactured LTCC coil for turbocharger speed sensors and its optimized signal output by the novel design.